Cholera toxin B subunit induces local curvature on lipid bilayers. Issue 11 (10th October 2017) - Pezeshkian, Weria; Nåbo, Lina J.; Ipsen, John H.
Abstract : The B subunit of the bacterial cholera toxin (CTxB) is responsible for the toxin binding to the cell membrane and its intracellular trafficking. CTxB binds to the monosialotetrahexosyl ganglioside at the plasma membrane of the target cell and mediates toxin internalization by endocytosis. CTxB induces a local membrane curvature that is essential for its clathrin‐independent uptake. Using all‐atom molecular dynamics, we show that CTxB induces local curvature, with the radius of curvature around 36 nm. The main feature of the CTxB molecular structure that causes membrane bending is the protruding alpha helices in the middle of the protein. Our study points to a generic protein design principle for generating local membrane curvature through specific binding to their lipid anchors. Abstract : The B subunit of the bacterial cholera toxin binds to lipid bilayers containing monosialotetrahexosyl ganglioside and induces local curvature. We have used all‐atom molecular dynamics to characterize the effect of toxin binding. The induced local curvature is essential for toxin internalization through both clathrin‐dependent and clathrin‐independent endocytosis.